CONTEMPORARY ECONOMIC GROWTH IN SUB-SAHARAN AFRICA: - Azenga, Festus Atem (Graduate School of International Studies Ajou University, 2013)
ABSTRACT In the second half of the 20th century, Sub-Saharan Africa was characterized with a picture of decay and despair. The region was adversely affected by extreme poverty, famine, authoritarian rule, and ongoing economic crises. For over fifty years, economic progress was lagging across the region with zero economic growth per capita. However, in the first decade of the 21st century major changes began to occur with most Sub-Saharan countries making remarkable economic progress for over 10 to 12 years. Numerous factors are at the root of this new economic progress including democratic reforms, a new security paradigm, debt relief, economic reforms, and new trade relations with Asia and the BRICS. Yet in the midst of this decade of change the economic growth was unevenly spread across the Sub-Saharan region where most groupings of states greatly outpaced the average growth of Africa’s Francophone states. After a decade of growth they lagged behind the average growth rates found in Anglophone, Lusophone, and Semitic states. The study will explain how such political, economic and security relationship between France and Francophone African countries has hindered development and economic growth in this region of the Sub-Saharan. Consequently, factors that accounts for the recent growth pattern in the regions turn to be lagging in the French group of countries leading to an imbalance in the growth across the region.
학위논문(석사)아주대학교 국제대학원 :국제개발협력과,2013. 8